Acupuncture for rehabilitation after surgery for cerebellopontine angle meningioma: A case report. Issue 32 (August 2019) - Han, Dexiong; Shen, Yejing; Hu, Hantong; Zhang, Ying; Li, Xingling; Fang, Lianqiang; Gao, Hong
Abstract: Rationale: In some cases, surgery of cerebellopontine angle meningioma (CPAM) might result in multiple cranial nerve injury, which could bring serious impact on the patients, especially when it affects the function of facial muscles and eyeballs. This report describes a successful application of acupuncture for rehabilitation in a patient after surgery for CPAM. Patient concerns: A 27-year-old patient presented with limitation of left eye abduction, accompanied with frontal and facial sensory disturbance on the left after resection of the pontocerebellar angle tumor. The patient also suffered from significant anxiety and depression as concomitant symptoms. Diagnoses: Based on medical history, clinical symptoms, and magnetic resonance imaging results, the patient was diagnosed with the fourth, fifth, sixth, and seventh cranial nerve injury after surgery for CPAM. Interventions: Acupuncture treatment was applied for this patient. One acupuncture session was given every 2 days in 35 days, and the needles were retained for 30 minutes per session. Outcomes: After acupuncture treatment, the limitation of left eye abduction had totally recovered. The superficial sensory disturbance in the frontal and facial region was significantly relived. Besides, the scores of Hamilton Anxiety and Depression Scale showed a significant reduction. However, the superficial sensory of the alar and nasolabial groove on the left side still decreased mildly when compared with the right side. Conclusion: Acupuncture might be an option for rehabilitation after surgery for CPAM.